Comparison of postoperative benign pelvic cysts occurred after gynecologic or gyne-oncologic surgery treated with percutaneous transcatheteric sclerosant alcohol therapy - Cihan Comba; Aysun Erbahceci Salik; Gokhan Demirayak; Sakir Volkan Erdogan; Filiz Sacan; Isa Aykut Ozdemir (Wolters Kluwer Medknow Publications, 2020)
Objectives: Here, we compare the success of percutaneous transcatheter sclerosant alcohol therapy (PTSAT) for the postoperative treatment of benign pelvic cysts that occurred after gynecologic surgery. Materials and Methods: The study is a retrospective case-control trial. Gynecological patients who had symptoms due to postoperative pelvic cysts and received PTSAT after gynecologic surgery, between October 2008 and January 2018, were examined in a single training and research hospital in Turkey. Some factors were investigated for associations with postoperative pelvic cyst formation in patients who underwent gynecologic operations for malignancies or benign conditions. Statistical analysis used: The association between two independent and nonnormally distributed continuous variables was analyzed with the Mann-Whitney U-test. Spearman's rho correlation analysis was conducted to determine the correlation of two nonnormally distributed variables. Chi-square (or Fisher's exact test, when more suitable) was used to examine the correlation between categorical variables. Results: Statistically significant differences were found in terms of the average age was higher in patients with malignancies, and the average postoperative pelvic cyst detection time was higher in patients with benign pelvic cysts. While all patients were treated with PTSAT, repetitive PTSAT was required for seven benign and ten malign cases. Conclusion: Patients with pelvic cysts that occurred after gynecologic surgery for malignant conditions, large volume pelvic cysts and patients with benign cysts who underwent more than one surgery required recurrent PTSAT.